Total Harmonic Distortion at Fault in RLC Load - Pankaj Aswal; Suyash Kumar Singh; Niharika Agarwal; Vivek Sharma; Gayatri Sharma (Institute of Advanced Engineering and Science, 2016)
This paper focuses on the calculation of total harmonic distortion (THD) at various fault situations in case of RLC load. The faults are created by introducing heavy impedance of 1000 ohm, by blowing off the gate pulse at one of the terminals of the mosfet, and by introducing a line to ground fault. The Matlab based simulation has been done to show these effects.